Identification of Mild Freezing Shock Response Pathways in Barley Based on Transcriptome Profiling - Wang, Xiaolei; Wu, Dezhi; Yang, Qian; Zeng, Jianbin; Jin, Gulei; Chen, Zhong-Hua; Zhang, Guoping; Dai, Fei (Frontiers in Plant Science, 2016)
Low temperature is a major abiotic stress affecting crop growth and productivity. A better understanding of low temperature tolerance mechanisms is imperative for developing the crop cultivars with improved tolerance. We herein performed an Illumina RNA-sequencing experiment using two barley genotypes differing in freezing tolerance (Nure, tolerant and Tremois, sensitive), to determine the transcriptome profiling and genotypic difference under mild freezing shock treatment after a very short acclimation for gene induction. A total of 6,474 differentially expressed genes, almost evenly distributed on the seven chromosomes, were identified. The key DEGs could be classified into six signaling pathways, i.e. Ca2+ signaling, PtdOH signaling, CBFs pathway, ABA pathway, jasmonate pathway and amylohydrolysis pathway. Expression values of DEGs in multiple signaling pathways were analyzed and a hypothetical model of mild freezing shock tolerance mechanism was proposed. Expression and sequence profile of HvCBFs cluster within Frost resistance-H2, a major quantitative trait locus on 5H being closely related to low temperature tolerance in barley, were further illustrated, considering the crucial role of HvCBFs on freezing tolerance. It may be concluded that multiple signaling pathways are activated in concert when barley is exposed to mild freezing shock. The pathway network we presented may provide a platform for further exploring the functions of genes involved in low temperature tolerance in barley.